Literature Review: Identification of Chemical Components and Antibacterial Activity of Cinnamon Bark Essential Oil (Cinnamomum burmanii) - Clarissa, Yesa Prilia; Mierza, Vriezka (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Bacterial infections remain a major global health concern, particularly with the growing incidence of antibiotic resistance. This situation has encouraged the search for alternative antibacterial agents derived from natural sources, including essential oils extracted from cinnamon bark. This review article aims to summarize current findings on the chemical characterization of cinnamon bark essential oil and the compounds responsible for its antibacterial activity, providing a foundation for its potential development as a natural antibacterial agent. Literature selection was conducted using specific inclusion and exclusion criteria, covering original research published between 2015 and 2025 and retrieved from PubMed and Google Scholar using the keywords “essential oil,” “Cinnamomum burmanii,” “bark,” and “antibacterial.” Based on this screening process, seven research articles met the established criteria. The reviewed data indicate that cinnamaldehyde is the predominant component of cinnamon bark essential oil and plays a major role in its broad spectrum antibacterial activity, including against resistant bacterial strains.